UJI AKTIVITAS ANTIBAKTERI Propionibacterium Acnes TERHADAP EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava L) - Farisa Luthfiana (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2024)
Acne is a common skin condition influenced by various factors, including Propionibacterium acnes infection.This study aims to evaluate the antibacterial activity of ethanol extract from guava leaves (Psidium guajava L.) against P. acnes and determine the most effective concentration for inhibiting bacterial growth. This research utilizes a quantitative approach using the disc diffusion method, with 96% ethanol extraction. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins, and quinones, which possess antibacterial properties. The antibacterial assay results indicate that the inhibition zones at concentrations of 25%, 50%, and 75% measured 5.67 mm, 12.4 mm, and 16.0 mm, respectively. In comparison, clindamycin (positive control) exhibited an inhibition zone of 21.84 mm, while the negative control (distilled water) showed no inhibitory effect.The findings of this study confirm that the ethanol extract of guava leaves demonstrates antibacterial activity against P. acnes, with the 75% concentration exhibiting the highest efficacy. However, its inhibitory effect remains lower than that of clindamycin, highlighting the need for further research to optimize its potential as anatural antibacterial agent.